Exploring medications for hypertension advertised online: A qualitative study in Indonesia - Riana Rahmawati (Wolters Kluwer Medknow Publications, 2020)
Introduction: Patients with hypertension often self-medicate and are increasingly purchasing their medications online. This study aimed to identify the medications and products used for hypertension offered by Indonesian online marketplaces and the availability of prescription-only antihypertensive medication on these platforms. Materials and Methods: This qualitative document analysis comprehensively assessed three online marketplaces in Indonesia in May 2019. Five top products in each online marketplace were identified and reviewed. An in-depth analysis was performed to obtain detailed information about the products (e.g., ingredients), indications, and customers' comments. Selected antihypertensive medications (captopril, amlodipine, and valsartan) were searched for. The data were analyzed thematically. Results: The search results showed that more than 5000 products were available in each online marketplace and that all of the top products offered in these platforms were traditional medicines. Some products specifically claimed to be effective for lowering blood pressure (e.g., "the solution for hypertension without complications"). Morinda citrifolia (noni) and Allium sativum (garlic) were ingredients found in all three platforms, mainly in combination with other herbal medicines. The prescription-only antihypertensive medications offered and could be purchased through online marketplaces reviewed. However, information about dosage forms, indications, side effects, and contraindications of these medications was rarely provided on these platforms. Conclusion: Indonesian online marketplaces provide a wide range of products for the treatment of hypertension, particularly traditional medicines. Given the increasing trends of online shopping, providing objective and adequate information for customers is essential. Regulations for the purchase of prescription-only medicines, such as antihypertensive medications, should be strengthened.